DETERMINAN KEJADIAN DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI - Christine Vita Gloria; Yuyun Priwahyuni; M. Dedi Widodo; Suci Fanesa (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
Diabetes Mellitus is abnormality of insulin hormone that is marked with high blood glucose levels. In indonsia, total of diabetes mellitus sufferer in 2000 is 8,4 million (7,8%) peoples and expected in 2030 will reached untll 21,3 million (9,1%) people. Diabetes mellitus case in work area of Public Health Centre (PHC) Payung Sekaki Pekanbaru City In 2017 is 1.798 (2,3%). This research purpose is to knowing determinants case of diabetes melliitus type 2 in work area PHC Payung Sekaki Pekanbaru City. This research method is quantitative with research type is observational analysis and this design research is case control. Technique Sampling which is used is Non Probability and Quota Sampling technique. Analysis of data what done is univariat and bivariat wit Chi Square test. The result research show that, there are corelation among age, obesity, exercise, eating pattern with Diabetes Mellitus Type 2 case, andthere is no corelation between family support with Diabetes Mellitus Type 2case. Suggestion for PHC, to do socialization about managed healthy life pattern, keep the ideal body weight, also helding the healthy gymnastics program in PHC in the morning as 3 times in a week.